Adsorption characteristics of the shale matrix in Mancos and Eagle Ford basins, USA. Issue 16 (17th August 2016) - Jang, Hochang; Kim, Changjae; Lee, Jeonghwan
ABSTRACT: This study presents an experimental apparatus to investigate the adsorption characteristics in shale samples of two major US basins. The adsorption measurement is based on volumetric method, and the results are analyzed by Langmuir isotherm at various pressures. To analyze the impact of temperature on the adsorption characteristics, the experiments were conducted on the samples. The experimental results revealed that the change of adsorption capacity became constant with the increase of pressure and the decrease of adsorption capacity was dependent on the increase of temperature. This study allows us to evaluate shale gas in place and production forecast through adsorption characteristics.